Cover Picture: Heterolytic Activation of H2 Using a Mechanically Interlocked Molecule as a Frustrated Lewis Base (Angew. Chem. Int. Ed. 3/2013). Issue 3 (11th December 2012) - Caputo, Christopher B.; Zhu, Kelong; Vukotic, V. Nicholas; Loeb, Stephen J.; Stephan, Douglas W.
<x xml:space="preserve">Abstract</x> The reactivity of frustrated Lewis pairs is induced by the utilization of a sterically unencumbered aniline as the axle in a [2]rotaxane. In their Communication on page 960 ff., S. J. Loeb, D. W. Stephan, and co‐workers show that the [2]rotaxane imparts enough steric bulk to the base to preclude adduct formation with B(C6F5)3. This unique modification also shows frustrated Lewis pair reactivity in the activation of H2 at room temperature.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>